A Study of Maiduguri Youths’ Perception of Online Shopping during the COVID-19 Lockdown - Moses, Jude Melea (Journal of Innovation in Academia, 2023)
This research examines youths’ perception of online shopping during the COVID-19 lockdown in Maiduguri, Nigeria. This study adopts a descriptive research design to fill the knowledge gap on the current state of e-shopping during the COVID-19 pandemic, a global public health emergency. The objectives of study are to examine the perceived knowledge, behaviours, benefits and risks of online shopping among youths during this period. Their perceptions of online shopping during COVID-19 have implications towards online shopping, COVID-19 compliance and health communication during health emergencies. The researcher administered 200 copies of questionnaires with a 97% return rate. The data collected were analysed using SPSS 15.1 version. Findings from the study revealed that the perceived benefit factors motivated youths to shop online in order to stop the spread of the coronavirus disease. The knowledge of youths in Maiduguri about online shopping also increased due to the government-imposed lockdown. Furthermore, the study also revealed that the internet was the major source of information on online shopping and mobile phones were the major devices used for online shopping in Maiduguri during the period of lockdown. This study recommends that managers of online stores should employ the best approach to ensure the safety and security of e-shoppers’ personal information.